2003
DOI: 10.2307/3345660
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Selected Variables on Solo and Small-Ensemble Festival Ratings

Abstract: With this study, we examined four potential influences on American high school solo and small-ensenble festival adjudicator ratings-time of day, performing medium (vocal or instrumental), type of event (solo or ensemble), and school size. A total of 7,355 instrumental and vocal events from two consecutive midwestern state solo and ensemblefestivals were analyzed. The twofestivals, held in 2001 and 2002, employed 75 adjudicators (33 vocal and 42 instrumental). Statistically significant differences were found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 16 publications
7
51
2
Order By: Relevance
“…Form B yielded significantly different ratings in every dimension except interpretation, suggesting that the adjudicators in this setting rated the choirs more severely when using Form B. This finding contradicts previous research (Bergee & Platt, 2003;Bergee & Westfall, 2005) (Asmus, 1999;Gordon, 2002;Whitcomb, 1999). The goal of all assessment research should focus on the development of reliable and valid tools that are specific enough to provide diagnostic feedback for conductors and performers, yet global enough to allow for artistic expression.…”
contrasting
confidence: 56%
“…Form B yielded significantly different ratings in every dimension except interpretation, suggesting that the adjudicators in this setting rated the choirs more severely when using Form B. This finding contradicts previous research (Bergee & Platt, 2003;Bergee & Westfall, 2005) (Asmus, 1999;Gordon, 2002;Whitcomb, 1999). The goal of all assessment research should focus on the development of reliable and valid tools that are specific enough to provide diagnostic feedback for conductors and performers, yet global enough to allow for artistic expression.…”
contrasting
confidence: 56%
“…Although cause and effect has yet to be established, these influences seem quite salient; they persist across time In accordance, a line of investigation has attempted to develop a theoretical model of key extramusical influences. In the first study in this series, Bergee and Platt (2003) examined four potential influences on state high school solo and small-ensemble festival ratingstime of day, performing medium (vocal or instrumental), type of event (solo or ensemble), and school size. A total of 7,355 instrumental and vocal events from two consecutive Midwestern state solo and small-ensemble music festivals (the 2001 and2002 Missouri State Music Festivals) were analyzed.…”
mentioning
confidence: 99%
“…For vocal entries, being part of an ensemble was beneficial, while instrumental soloists tended to be more highly rated than ensemble entries. Bergee and McWhirter (2005) sought to replicate Bergee and Platt's (2003) study and confirmed the findings from the earlier research. They also investigated the impact of school district expenditure and found, not surprisingly, that increased spending resulted in higher festival results.…”
Section: Research Related To the Adjudication Processmentioning
confidence: 71%
“…Bergee and Platt (2003) identified time of day, school size and whether the performance was by a solo or ensemble as factors that influence how many superior ratings are awarded in a solo and small-ensemble festival competition. Competitors who came from larger schools and who performed in the afternoon were more likely to receive high ratings.…”
Section: Research Related To the Adjudication Processmentioning
confidence: 99%
See 1 more Smart Citation